Awerroes, czyli losy filozofii arabskiej w świecie łacińskim = Averroes or the fate of the Arab philosophy in the Latin language world - Palacz, Ryszard (1935-2024) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article briefly discusses the impact of Averroism on the philosophy of Latin Europe in the thirteenth century. The heritage of Greek philosophy and science was saved by Arab scholars, and in the field of philosophy mainly by Averroes and his followers, which enabled the reception of Aristotle's thought in Europe. At the University of Paris, Averroes` commentaries on Aristotle`s treatises not only led to disputes in the Philosophy Faculty, but also deepened the doctrinal differences that existed in teaching between faculties.
Keywords: philosophy; Averroism; University of Paris; reception of Aristotle; filozofia; awerroizm; Uniwersytet Paryski; Arystoteles (filozof; 384 p.n.e.-322 p.n.e.) - recepcja